Evidence of relationships between teachers' leadership style practices for learning and student academic press/Emphasis. - Kunalan, Hemathy; Mohd Ali, Hairuddin; Nordin, Mohamad Sahari (2018)
The purpose of the study was to investigate the relationship between teachers’ leadership styles practices for learning with students’ academic press/emphasis (AP/AE) at selected secondary schools in Kuala Lumpur. The study employed a quantitative research design to address the research problems and two research hypotheses. A total of 328 students from three selected secondary schools in Kuala Lumpur was randomly selected to complete the survey questionnaires of the study. The data were statistically analysed using confirmatory factor analysis and structural equation modelling. The results showed that the English subject teachers at the selected national secondary schools exhibited clearly the two leadership styles practices (COE and COA) as it supported the hypotheses that the two predictors were adequate to explain students’ AP/AE, particularly COA which was the most influential predictor. This study therefore adds a new dimension to the body of knowledge that will help researchers’ efforts to understand the relationship between English subject teachers’ leadership styles practices and students’ AP/AE. As this study takes place in the Malaysian context, it definitely contributes to the enriching of the indigenous body of knowledge. The implication would be in terms of the teacher training and enhancement of teacher professional development programmes.